2017
DOI: 10.1039/c7cp01971h
|View full text |Cite
|
Sign up to set email alerts
|

Direct experimental observation of mesoscopic fluorous domains in fluorinated room temperature ionic liquids

Abstract: Fluorinated room temperature ionic liquids (FRTILs) represent a class of solvent media that are attracting great attention due to their IL-specific properties as well as features stemming from their fluorous nature. Medium-to-long fluorous tails constitute a well-defined apolar moiety in the otherwise polar environment. Similarly to the case of alkyl tails, such chains are expected to result in the formation of self-assembled fluorous domains. So far, however, no direct experimental observation has been made o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
36
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 109 publications
5
36
0
Order By: Relevance
“…Although the presently considered anion is different from [TFSI] that was studied in reference 56 , we can determine that the occurrence of this HB interaction is quite rare with the present choice of cation and anion: the integrated number of neighbour anion nitrogen around the reference cation hydrogen is <0.1 for r<3 Å (corresponding to Recently, we undertook a series of investigations on a variety of AILs containing fluorous chains in their anions. 36,48,55,[57][58][59][60] Therein, we observed that, in agreement with other experimental 61 Figure 2), that typically would fingerprint the existence of segregated domains with mesoscopic spatial extent. 36,48,55,[57][58][59][60] Recently, we showed in a number of examples that while neutrons can successfully appreciate such a feature, due to contrast reasons, X-ray may fail to detect it.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Although the presently considered anion is different from [TFSI] that was studied in reference 56 , we can determine that the occurrence of this HB interaction is quite rare with the present choice of cation and anion: the integrated number of neighbour anion nitrogen around the reference cation hydrogen is <0.1 for r<3 Å (corresponding to Recently, we undertook a series of investigations on a variety of AILs containing fluorous chains in their anions. 36,48,55,[57][58][59][60] Therein, we observed that, in agreement with other experimental 61 Figure 2), that typically would fingerprint the existence of segregated domains with mesoscopic spatial extent. 36,48,55,[57][58][59][60] Recently, we showed in a number of examples that while neutrons can successfully appreciate such a feature, due to contrast reasons, X-ray may fail to detect it.…”
supporting
confidence: 91%
“…36,48,55,[57][58][59][60] Therein, we observed that, in agreement with other experimental 61 Figure 2), that typically would fingerprint the existence of segregated domains with mesoscopic spatial extent. 36,48,55,[57][58][59][60] Recently, we showed in a number of examples that while neutrons can successfully appreciate such a feature, due to contrast reasons, X-ray may fail to detect it. 36,55,[57][58][59][60]66 Neutron diffraction measurements therefore might indicate the presence of a further low Q peak centred at ca.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Results from ab initio calculations, carried out on other pyrrolidinium-based ILs, are in agreement with the heteronuclear NOE measurements, which show anion interactions with the cation ring [14]. The spatial segregation of fluorinated chains, in asymmetric bis(perfluoroalkylsulfonyl)imide anions, into nm-sized heterogeneities was also evidenced by Lo Celso et al [15,16] through small angle X-ray and neutron scattering. Before that, experimental X-ray scattering experiments [17] and Molecular Dynamics simulations [18] in protic ILs with fluorinated chains showed related observations, although influenced by the strong hydrogen bonding interactions between opposite ions.…”
Section: Introductionsupporting
confidence: 82%
“…Besides the multiple applications, IL either with or without dilution also pose several physicochemical properties that extend the phenomenology of concentrated electrolytes: (i ) multiple timescales, 17,32 (ii ) self-assembly, [33][34][35] and (iii ) non-monotonic variation (exhibiting qualitatively three distinct regions) of EDL with concentration, 15,36 a.k.a., the phenomenon of under-screening. These phenomenologies emphasize that besides the vast progress in concentrated electrolytes, a unified framework that combines altogether the above mentioned phenomena is still missing.…”
mentioning
confidence: 99%